1990
DOI: 10.1002/jsfa.2740510403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of germination on the chemical composition of Glycine and Phaseolus beans

Abstract: A B S T R A C TThe effects of germination on total protein and amino acids, and phytic acid of beans of Glycine max L , Glycine hispida L, Phaseolus radiatus L and Phaseolus angularis L were studied. The increase in total crude protein content was > 21 % for Glycine beans and 8-15 % for Phaseolus beans.There was a marked increase in the total essential amino acids of Glycine max (76%) and Phaseolus radiatus (52%). A smaller increase was observed for Phaseolus angularis (25 %) and Glycine hispida (3 %). The phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1
3

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 24 publications
4
24
1
3
Order By: Relevance
“…Similar findings were reported by Akinlosotu and Akinyele (1991). Lee and karunanithy (1990) observed also an increase in total crude protein content of more than 21% in dehulling germinated soybean compared to ungerminated seeds. AwadAllah (1996) observed that the protein content was (37.61%) in soybean seed variety "Calland" which was characterized by relatively less lipid content (19.16%).…”
Section: Resultssupporting
confidence: 89%
“…Similar findings were reported by Akinlosotu and Akinyele (1991). Lee and karunanithy (1990) observed also an increase in total crude protein content of more than 21% in dehulling germinated soybean compared to ungerminated seeds. AwadAllah (1996) observed that the protein content was (37.61%) in soybean seed variety "Calland" which was characterized by relatively less lipid content (19.16%).…”
Section: Resultssupporting
confidence: 89%
“…No difference in iron content was observed when raw sprouts were subjected to either pressure cooking or microwaving. Lee and Karunanithy (1990) found that the loss of iron was less during germination. However, longer cooking periods i.e.…”
Section: Resultsmentioning
confidence: 98%
“…A minimal reduction (0.3 to 3.2%) was seen in three legumes after two heat treatments. Lee and Karunanithy (1990) and Barakoti and Bains (2007) found that calcium was low in germinated legumes when compared to raw. Rincon et al (1993) observed a significant loss of calcium in cowpea during pressure cooking.…”
Section: Resultsmentioning
confidence: 99%
“…Soymilk prepared by traditional method presents some problems and many workers have tried to improve the quality by elimination of off flavour (Nelson et al 1976;Matsuura et al 1989); inhibiting the anti nutritional factors (Luttrell et al 1981;Weingartner 1987); reducing the phytic acid content (Ologhobo and Fetuga 1984); improving soymilk yield (Lee and Karunanithy 1990) etc. All these efforts generally take care of one or two of the problems associated and use heat intensive methods for anti-nutrient reduction thereby reducing the overall nutritional quality of soymilk.…”
Section: Introductionmentioning
confidence: 99%